Resolubilidade global de operadores lineares com coeficientes constantes - Carpes, Hekatelyne Prestes (2013)
In this dissertation we present a proof of a Bernard Malgrange theorem, which establishes a necessary and sufficient condition for the global solvability of a linear operator with constant coefficients.